Pengaruh Musik Klasik Terhadap Penurunan Tekanan Darah Ibu Hamil Dengan Hipertensi di Puskesmas Beringin Jaya - Damayanti S, Grace Erlyn (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Preeclampsia in pregnancy affects both maternal and perinatal outcomes. One of the signs and symptoms of preeclampsia is the occurrence of hypertension. Hypertension in preeclampsia is found in pregnant mothers with gestational age > 20 weeks. Management efforts of hypertensive disease and its possible complications need to be improved to decrease morbidity and mortality rates. Music therapy is a form of activity that uses music and songs/songs integrated and directed in guiding the mothers during pregnancy intended to achieve the goals: relaxation for expectant mothers, early stimulation of the fetus, establishment of emotional attachment between mothers. The aim of this study was to know the influence of classical music on blood pressure reduction in pregnant mothers with hypertension in Beringin Jaya Health Center. The study is a quantitative research in nature Quasi Experiment with pre test and posttest design. The population of this study was all pregnant mothers with hypertension visiting Beringin Jaya Health Center. A total of 13 individuals were obtained by accidental sampling technique. The statistical test used was a paired sample t test with a confidence level of 95% (? = 0.05). The results of this study showed there was an influence of classical music on blood pressure reduction in pregnant mothers with hypertension in Beringin Jaya Health Center (p value 0.000). It is therefore expected for midwives in health centers to implement classical music administration as one of the interventions to lower blood pressure in pregnant mothers with hypertension.